1979
DOI: 10.1002/chin.197915084
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: STRUCTURAL STUDIES OF 1,8‐DISUBSTITUTED NAPHTHALENES AS PROBES FOR NUCLEOPHILE‐ELECTROPHILE INTERACTIONS

Abstract: Gemeinsame Merkmale der röntgenographisch ermittelten Molekülstrukturen der Naphthaline (I)‐(III) (in Klammern Raumgruppe, Z) sind eine Neigung der exocyclischen Bindung zum nukleophilen Zentrum einwärts (in Rich‐ i. tung auf die Verlängerung der zentralen Bindung des Naphthalinsystems) und eine Auswärtsneigung der Bindung zum elektrophilen Carbony1‐Substituenten.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1982
1982
1989
1989

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…and C0,Et groups is 2.665 P\ whereas the corresponding distances in compound (5) are 3.363 and 3.1 50 A. The results demonstrate the existence of an attractive nucleophile-electrophile interaction in (4).…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…and C0,Et groups is 2.665 P\ whereas the corresponding distances in compound (5) are 3.363 and 3.1 50 A. The results demonstrate the existence of an attractive nucleophile-electrophile interaction in (4).…”
mentioning
confidence: 74%
“…carbonyl C, at the other. 4 The compounds (7) do not suffer the usual repulsive interactions that characterise other 1,8disubstituted naphthalenes and their N C distances of ca.…”
mentioning
confidence: 99%
“…Next, reactions of the trans-epoxides with lithium dimethylcuprate were examined. It was found that, whereas treatment of the acetoxy epoxide (24) with an excess of lithium dimethylcuprate gave a complex mixture of products, the correponding benzyl ether epoxide (29) reacted cleanly and gave the expected alcohol (37) in good yield (85%). The benzoyloxy epoxide (26) was intermediate in behaviour, the alcohol (38) being isolated in 44% yield, and the p-methoxybenzoyloxy epoxide (27) was slightly better giving 55% of chromatographed alcohol (39).…”
Section: Rzo -1\1mentioning
confidence: 99%
“…The major epoxide in each case was identified as the trans-epoxide, i.e. (24)- (29). This stereoselectivity was predicted assuming the conformation shown in structure A,* 9' ' the axial allylic alkoxycarbonyl substi tuent providing more steric hindrance to epoxidation than the equatorial allylic methyl substituent ; the epoxidation of 4-acetoxy-2,6,6-trimethylcyclohexene (36) provides an analogy.…”
mentioning
confidence: 94%